DIALOGUE BETWEEN ISLAM AND ENVIRONTMENTAL ETHICS THROUGH THE SEYYED HOSSEIN NASR THOUGHT - Nugraha, Aulia Rahman; Asnawi, Naupal (International Review of Humanities Studies, 2019)
Islam is often regarded as a religion that teaches anthropocentrism through the concept of the caliph in which humans occupy a central position on earth. However, the concept of the caliph itself is a complex concept where the special status of humans always implies a moral obligation. Through alternative explanatory methods and critical reflection, the authors try to clarify the concept of the caliph and show the teachings of Islam that are environmentally friendly through the thought of Seyyed Hossein Nasr. Philosophy and environmental ethics of Nasr have two major projects, namely the resacralization of nature and the clarification of the concept of the caliph through Insan Kamil. For Nasr, man has the ability to control nature, and therefore he must increase his spirituality in the light of monotheism to understand nature holistically. A holistic understanding of nature opens the awareness that humans and nature have intimate, anthropocosmic relationships in which both share the same archetype. The Islamic environmental ethics approach of Nasr seeks to show that Islamic teachings maintain human and natural values without reducing one of the two. The conclusions in this paper show that Islam is compatible with environmental ethics insofar as the interpretation is aimed at this. Islam teaches respect for nature since the concept of the caliph shows that humans have responsibilities and intimate relationships with their environment.